Pyrrole acetylenecarbaldehydes: an entry to a novel class of functionalized pyrroles. Issue 45 (9th November 2016) - Gotsko, Maxim D.; Sobenina, Lyubov N.; Tomilin, Denis N.; Markova, Marina V.; Ushakov, Igor A.; Vakul'skaya, Tamara I.; Khutsishvili, Spartak S.; Trofimov, Boris A.
Graphical abstract: Highlights: The first synthesis of 3-(pyrrol-2-yl)propiolaldehydes was described. The method is solvent-free and transition metal-free, and utilized mechanoactivation in a solid K2 CO3 medium. The likely mechanism of the cross-coupling implies the one-electron transfer from the pyrrole to iodopropiolaldehyde. Abstract: The first representatives of a previously unknown class of highly reactive functionalized pyrrole compounds, 3-(pyrrol-2-yl)propiolaldehydes, have been synthesized by the transition metal-free, mechanoactivated ethynylation of pyrroles with 3-iodopropiolaldehyde using a solid K2 CO3 medium under mild conditions (room temperature, 4 h) in yields of up to 71%.